2014 Myanmar Enterprise Survey : Country Highlights - World Bank Group (Washington, DC, 2014)
Private sector firms in Myanmar have reported spectacular sales growth since the onset of a series of government-initiated policy reforms in 2011. A 24 percent real annual sales growth rate puts Myanmar in the fastest growing private sectors as measured by Enterprise Surveys (ES). The employment growth rate is positive but lower than the average of the economies in East Asia and Pacific (EAP). Importantly, this remarkable sales growth took place despite great hurdles (see below), which is suggestive of continued growth that could be unlocked by further reforms. As Myanmar continues to open up to foreign investment, this growth will likely continue.